An Aγ-globin G->A gene polymorphism associated with β039 thalassemia globin gene and high fetal hemoglobin production - Giulia Breveglieri; Nicoletta Bianchi; Lucia Carmela Cosenza; Maria Rita Gamberini; Francesco Chiavilli; Cristina Zuccato; Giulia Montagner; Monica Borgatti; Ilaria Lampronti; Alessia Finotti; Roberto Gambari (BMC, 2017)
Abstract Background Increase of the expression of γ-globin gene and high production of fetal hemoglobin (HbF) in β-thalassemia patients is widely accepted as associated with a milder or even asymptomatic disease. The search for HbF-associated polymorphisms (such as the XmnI, BCL11A and MYB polymorphisms) has recently gained great attention, in order to stratify β-thalassemia patients with respect to expectancy of the first transfusion, need for annual intake of blood, response to HbF inducers (the most studied of which is hydroxyurea). Methods Aγ-globin gene sequencing was performed on genomic DNA isolated from a total of 75 β-thalassemia patients, including 31 β039/β039, 33 β039/β+IVSI-110, 9 β+IVSI-110/β+IVSI-110, one β0IVSI-1/β+IVSI-6 and one β039/β+IVSI-6. Results The results show that the rs368698783 polymorphism is present in β-thalassemia patients in the 5'UTR sequence (+25) of the Aγ-globin gene, known to affect the LYAR (human homologue of mouse Ly-1 antibody reactive clone) binding site 5'-GGTTAT-3'. This Aγ(+25 G->A) polymorphism is associated with the Gγ-globin-XmnI polymorphism and both are linked with the β039-globin gene, but not with the β+IVSI-110-globin gene. In agreement with the expectation that this mutation alters the LYAR binding activity, we found that the Aγ(+25 G->A) and Gγ-globin-XmnI polymorphisms are associated with high HbF in erythroid precursor cells isolated from β039/β039 thalassemia patients. Conclusions As a potential explanation of our findings, we hypothesize that in β-thalassemia the Gγ-globin-XmnI/Aγ-globin-(G->A) genotype is frequently under genetic linkage with β0-thalassemia mutations, but not with the β+-thalassemia mutation here studied (i.e. β+IVSI-110) and that this genetic combination has been selected within the population of β0-thalassemia patients, due to functional association with high HbF. Here we describe the characterization of the rs368698783 (+25 G->A) polymorphism of the Aγ-globin gene associated in β039 thalassemia patients with high HbF in erythroid precursor cells.